1995
DOI: 10.1139/b95-124
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sand deposition on the interaction between Ammophila arenaria, plant-parasitic nematodes, and pathogenic fungi

Abstract: Arnrnophila arenaria is a dominant sand-fixing plant species of the European coastal foredunes. It remains vigorous under regular burial conditions on seaward slopes, but starts to degenerate when sand accumulation diminishes. Several hypotheses have been put forward to explain this degeneration. In this study, we test the hypothesis that upward growth of plants following sand burial enables them to escape harmful soil organisms. Plants in a degenerating field stand of A. arenaria and potted plants grown in st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Plants in the field must therefore be able to overcome the proposed negative feedback. The mass of shoots and below‐ground stems (rhizomes) were not determined, but previous studies have demonstrated a mass gain in these plant organs over the growing season (De Rooij‐Van der Goes et al . 1995b).…”
Section: Discussionmentioning
confidence: 99%
“…Plants in the field must therefore be able to overcome the proposed negative feedback. The mass of shoots and below‐ground stems (rhizomes) were not determined, but previous studies have demonstrated a mass gain in these plant organs over the growing season (De Rooij‐Van der Goes et al . 1995b).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the amount of deposition also affects the vitality of marram grass (De Rooij-Van Der Goes et al, 1995;Disraeli, 1984;Konlechner et al, 2013;Maun, 1998;Van der Putten and Peters, 1997). Marram grass requires a certain amount of burial for optimal growth.…”
Section: Vegetation-sedimentation Interactionsmentioning
confidence: 99%
“…In foredunes, both understory cover and light intensity were lower in P. nigra stands than in Populous deltoides stands (Figs. Alternatively, increased intensity of pathogens and decreased sand burial may limit the growth of the foredune grasses in stabilized sand in pine stands relative to the more dynamic Populus deltoides stands (de Rooij-van der Goes et al 1995 The wetpanne habitat provided an opportunity to compare the effects of the introduced pine with those of a native pine on abiotic and biotic components of the wetpanne. 5a), but species richness and solum thickness did not differ ( Fig.…”
Section: Functional Equivalency Of P Nigra Stands and Stands Of Natimentioning
confidence: 99%